Linear low density polyethylene/poly (vinyl alcohol)/kenaf composites: effect of natural weathering on functional group, weight loss characteristics, tensile, morphological and thermal properties - Pang, Ai Ling; Hanafi Ismail; Azhar Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2018)
The development of natural fiber polymer composites is increasing worldwide and in some applications, these composites are used at outdoor rendering them exposed to ultra-violet (UV) radiation. The paper investigates the degradation behavior of linear low density polyethylene/poly (vinyl alcohol)/kenaf (LLDPE/PVOH/KNF) composites after exposure to different natural weathering durations. The composites with KNF loadings of 10, 20 and 40 parts per hundred resin (phr) were exposed to natural weathering for 3 months and 6 months, respectively. The weathered composites were characterized by Fourier transform infrared (FTIR) spectroscopy, universal testing machine, field emission scanning electron microscopy (FESEM) and differential scanning calorimetry (DSC). The FTIR analysis showed an obvious carbonyl peak in composites after weathering as an evidence of oxidation. The weight loss percentage of composites increased with respect to exposure duration due to higher absorption of UV irradiation. The tensile properties of weathered composites were lower than that of control composites and these properties also decreased with increasing exposure duration. FESEM micrographs illustrated that composites with longer exposure duration suffered more surface damaged. The crystallinity percentage was found to increase with increasing exposure duration.